The unauthorized version : truth and fiction in the Bible - Fox, Robin Lane, 1946- (New York : Vintage Book, 1992)
Originally published: London: Viking Penguin, 1991
Includes bibliographical references and index
Keywords: Bible -- Evidence, authority, etc; Bible -- Controversial literature